The Effectiveness Of Health Education On Compliance With The Health Protocol Of The Covid19 Pandemic In The Community Of Bulurejo Village, Benjeng District Gresik - Danni Tri Juansa; Muhammad Ali Sodik (Universitas STRADA Indonesia, 2020)
Coronaviruses are a large family of viruses that cause disease in humans and animals. In humans, it usually causes respiratory tract infections, ranging from the common cold to serious diseases such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). The purpose of this study is to analyze The effect of health education on compliance with the COVID-19 pandemic health protocol in the community in Bulurejo Village, Benjeng District, Gresik Regency. The design of this research is an experimental quantitative study with a Quasy Pre Post Experimental approach with the focus of the research being directed at analyzing the effect of health education on compliance with the covid-19 pandemic health protocol in the community in Bulurejo Village, Benjeng District, Gresik Regency with a population of 74 respondents and a sample of 58 respondents taken by the Accidental Sampling technique. The findings show that shave not been given health education most of the respondents 42 respondents did not comply with health protocols (73.3%). After being given health education, most of the respondents complied with health protocols as many as 37 respondents (63.8%).Research results using Paired T-Test This shows that the p-value is 0.000 <0.05, then H0 is rejected and H1 is accepted, so it can be concluded that there is an effect of health education on compliance with the COVID-19 pandemic health protocol in the community in Bulurejo Village, Benjeng District, Gresik Regency.. It is hoped that the public can comply with health protocols as they should where they must use standard masks, keep their distance and diligently wash their hands with soap. This will reduce the risk of spreading the Covid-19 virus.